The Effects of Different Smoking Patterns in Pregnancy on Perinatal Outcomes in the Southampton Women's Survey - Hayes, Catherine (My University, 2020)
Maternal smoking during pregnancy has established associations with poor perinatal outcomes. Among continuing pregnant smokers, harm-reduction strategies have been suggested, including temporary cessation of smoking during pregnancy, also known as partial quitting. Support for this strategy, however, remains limited. Six hundred and ninety-seven women in the Southampton Women’s Survey who smoked at their last menstrual period were categorised into sustained quitters, partial quitters (quit in either the first or third trimester but not both) or sustained smokers (continued to smoke throughout pregnancy). In regression models, compared with infants born to sustained smokers, infants born to sustained quitters and partial quitters were heavier at birth by β = 0.64 standard deviations (SD) (WHO z-score) (95% CI: 0.47–0.80) and 0.48 SD (WHO z-score) (95% CI: 0.24–0.72) respectively, adjusted for confounders, with similar patterns seen for other anthropometric measures (head circumference and crown–heel length). Sustained quitters had longer gestations by β = 3.5 days (95% CI: 1.8–5.2) compared with sustained smokers, but no difference was seen for partial quitters. While sustained quitting remains the most desired outcome for pregnant smokers, partial quitting should be explored as a strategy to reduce some of the harmful effects of smoking on offspring in those who cannot achieve sustained quitting.
PUBLISHED
Keywords: Smoking; Pregnancy; Partial quitting; Perinatal outcomes; Birthweight; Gestation; Head circumference; Crown–heel length; Anthropometry